Students’ Perception of Teacher’s Bilingual Language Use in an English Classroom - Ni Putu Ines Marylena Candra Manik; Kadek Darmo Suputra (UHN IGB Sugriwa Denpasar, 2023)
In Indonesia, English is a subject taught start from primary school to university. However, in learning English students have difficulty in understanding the teachers’ instructions. Bilingual language is used by the teachers in delivering material because they believed the students’ get advantages. As a result, this study aimed to investigate students' perceptions of the use of English and Indonesian by teachers in teaching and learning in English classroom and to find out the benefits for students in learning English. The design of this research was descriptive in the form of qualitative. The number of subjects in this study were 33 students of 9th grade students SMP Pelangi Dharma Nusantara. The data used in this study were obtained through questionnaires and interviews. The results showed that students gave positive perceptions of the teacher's bilingual language (English and Indonesian) in the English classroom and it provided benefits for students such as easily understood the material, made the situation more comfortable, understood the instructions that were given by the teacher and increased confidence in participate in learning English.